2019
DOI: 10.1039/c8ra10306b
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and electrochemical properties of Li2M(WO4)2 (M = Ni, Co and Cu) compounds

Abstract: Li2M(WO4)2 (M = Co, Cu or Ni) materials have been synthesized using the solid-state reaction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The presence of multivalent ions in this sample and associated hopping events may be the cause of the dielectric behavior seen in the NaMnPO 4 compound. Several findings suggested that adding Mn to the mix resulted in a drop in the dielectric constant [72] . Although locking through charge‐balanced couplings between distinct ions found at various valence levels may reduce polarization, electron jumping between similar ions living in different valence states can boost polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of multivalent ions in this sample and associated hopping events may be the cause of the dielectric behavior seen in the NaMnPO 4 compound. Several findings suggested that adding Mn to the mix resulted in a drop in the dielectric constant [72] . Although locking through charge‐balanced couplings between distinct ions found at various valence levels may reduce polarization, electron jumping between similar ions living in different valence states can boost polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity is a thermally activated process that relies on the ordered movement of lightly bound charged particles while being affected by a continuous electric field. The following equation can be used to determine the electrical conductivity of the grain ( σ g ) at each temperature, derived from the resistance values obtained from the equivalent circuit: 28 where R g is the resistance of grain determined by the adjustment, S is the area of the electrode that is deposited on the pellet, and e is the thickness of the sample.…”
Section: Resultsmentioning
confidence: 99%